Perceptions of 24/7 In‐house Attending Coverage on Fellow Education and Autonomy in a Pediatric Cardiothoracic Intensive Care Unit. (15th April 2015) - Owens, Sonal T.; Owens, Gabe E.; Rajput, Shaili H.; Charpie, John R.; Kidwell, Kelley M.; Mullan, Patricia B.
Abstract Background The 24/7 in‐house attending coverage is emerging as the standard of care in intensive care units. Implementation costs, workforce feasibility, and patient outcomes resulting from changes in physician staffing are widely debated topics. Understanding the impact of staffing models on the learning environment for medical trainees and faculty is equally warranted, particularly with respect to trainee education and autonomy. Objective This study aims to elicit the perceptions of pediatric cardiology fellows and attendings toward 24/7 in‐house attending coverage and its effect on fellow education and autonomy. Methods We surveyed pediatric cardiology fellows and attendings practicing in the pediatric cardiothoracic intensive care unit (PCTU) of a large, university‐affiliated medical center, using structured Likert response items and open‐ended questions, prior to and following the transition to 24/7 in‐house attending coverage. Results All (100%) trainees and faculty completed all surveys. Both prior to and following transition to 24/7 in‐house attending coverage, all fellows, and the majority of attendings agreed that the overnight call experience benefited fellow education. At baseline, trainees identified limited circumstances in which on‐site attending coverage would be critical. Preimplementation concerns that 24/7 in‐house attending coverage would negatively affect the education of fellows were not reflected following actual implementation of the new staffing policy. However, based upon open‐ended questions, fellow autonomy was affected by the new paradigm, with fellows and attendings reporting decreased "appropriateness" of autonomy after implementation. Conclusions Our prospective study, showing initial concerns about limiting the learning environment in transitioning to 24/7 in‐house attending coverage did not result in diminished perceptions of the educational experience for our fellows but revealed an expected decrease in fellow autonomy. The study indirectly facilitated open discussions about methods to preserve fellow education and warranted autonomy in our PCTU; however, continued efforts are needed to achieve the optimal balance between supervised training and the transition to autonomous practice.